Exo-circRNAs: a new paradigm for anticancer therapy - Hetian Bai; Kexin Lei; Fei Huang; Zhou Jiang; Xikun Zhou (Molecular Cancer, 2019)
Abstract CircRNAs, as new members of long noncoding RNAs, have been the focus of recent investigation. CircRNAs feature a closed continuous loop structure without 5′-3′ polarity or a poly A tail. Many studies have reported the potential application of circRNAs in the clinic as new biomarkers and therapeutic targets in different diseases, especially for cancer. Additionally, the exosomes are important vehicles in cell-to-cell communication. And exo-circRNAs are circRNAs in exosomes which can be detected to provide additional evidence for conventional diagnostic methods and can be applied to suppress the malignant progress in cancer. In this review, we describe the biogenesis, characteristics, and functions of circRNAs and exosomes. Specifically, we present a comprehensive update of the promising role of exo-circRNAs in anticancer therapy.